Power Outages and the Performance of Small and Medium Scale Enterprises (SMEs) in Ekiti State, Nigeria - Akomolafe, Kehinde John Akomolafe (African Journal of Stability and Development (AJSD), 2024)
This study was carried out to examine the effects of power outages on the performance of SMEs in Ekiti State, Nigeria. The study was carried out in Ado-Ekiti, the state capital. Data were collected through the use of questionnaire, copies of which were administered to 114 SMEs in the study area. The findings show that on average, SMEs in the study area had access to electricity for about two days weekly, and it was only stable for between 1 hour and 5 hours daily. Similarly, the average monthly cost of electricity from the national grid was between about N5000 and N10, 000, while it costs SMEs between N30,000 and N90,000 monthly on average to fuel alternative electricity generators. The effect of power outages is negative on SMEs’ turnover. The study recommends that the government needs to provide palliatives to SMEs that would help reduce the burden of the power outage on the SMEs’ operations. This can be done through giving them tax incentives or subsidies.